2018
DOI: 10.12669/pjms.342.13848
|View full text |Cite
|
Sign up to set email alerts
|

Nonfasting Apo-lipoprotein B & Triglyceride levels as a predictor of coronary heart disease in Type II diabetic patients

Abstract: Background & Objectives:Lipoprotein-A has been recognized as a risk factor for ischemic heart diseases. Myocardial infarction (MI) is common complication of ischemic heart disease. Diabetes play an incremental role in the development of coronary artery disease (CAD), however still there are conflicting data regarding the relationship of Lipoprotein-B and MI. We therefore wanted to evaluate the relationship of Lipo-B, MI and diabetes mellitus. Our objective was to determine the non-fasting Apo-lipoprotein B and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Coronary artery disease (CAD) is a multifactorial disease in which atherosclerotic plaque accumulates inside the coronary arteries resulting in myocardial infarction and mortality. Hypertriglyceridemia is significantly associated with the increased risk of CAD, as elevated levels of triglycerides (TG) may lead to plaque formation [39][40][41]. e APOA5/4/ C3/A1 gene cluster on chromosome 11q23 plays an important role in TG regulation; particularly variants occurring in the APOA5 gene have been extensively analyzed for their relationship with TG metabolism and cardiovascular diseases susceptibility [34,36,42].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery disease (CAD) is a multifactorial disease in which atherosclerotic plaque accumulates inside the coronary arteries resulting in myocardial infarction and mortality. Hypertriglyceridemia is significantly associated with the increased risk of CAD, as elevated levels of triglycerides (TG) may lead to plaque formation [39][40][41]. e APOA5/4/ C3/A1 gene cluster on chromosome 11q23 plays an important role in TG regulation; particularly variants occurring in the APOA5 gene have been extensively analyzed for their relationship with TG metabolism and cardiovascular diseases susceptibility [34,36,42].…”
Section: Discussionmentioning
confidence: 99%
“…China is facing a growing aging population, leading to increased incidence and mortality from cardiovascular and cerebrovascular diseases, including AMI. 5 , 6 PCI via the radial artery can quickly restore coronary blood supply and improve myocardial blood supply, and is therefore recommended in AMI treatment guidelines. PCI is conducive to early rehabilitation exercise, and some studies have shown that early rehabilitation is beneficial for AMI patients.…”
Section: Discussionmentioning
confidence: 99%